Citric acid assisted phytoextraction of nickle from soil helps to tolerate oxidative stress and expression profile of NRAMP genes in sunflower at different growth stages - Ijaz, Munazza; Ansari, Mahmood-ur-Rahman; Alafari, Hayat Ali; Iqbal, Muhammad; Alshaya, Dalal S.; Fiaz, Sajid; Ahmad, Hafiz Muhammad; Zubair, Muhammad; Ramzani, Pia Muhammad Adnan; Iqbal, Javed; Abushady, Asmaa M.; Attia, Kotb (Frontiers in Plant Science, 2022)
Soil pollution polluted with Nickel (Ni) adversely affects sunflower growth resulting in reduced yield. Counterbalancing Ni toxicity requires complex molecular, biochemical, and physiological mechanisms at the cellular, tissue, and whole plant levels, which might improve crop productivity. Different plant varieties possess variable tolerance to stress conditions. One of the primary adaptations to tolerate Ni toxicity is the enhanced production of antioxidant enzymes and the elevated expression of Ni responsive genes. In this study, biochemical parameters, production of ROS, antioxidants regulation, and expression of NRAMP metal transporter genes were studied under Ni stress in sunflower. There were four soil Ni treatments (0, 50, 100, and 200 mg kg‒1 soil), while citric acid (CA, 5 mM kg‒1 soil) was applied on the 28th and 58th days of plant growth. The samples for all analyses were obtained on the 30th and 60th day of plant growth, respectively. The results indicated that the concentrations of Ni in roots and shoots were increased with increasing concentrations of Ni at both time intervals. Proline contents, ascorbic acid, protein, and total phenolics were reduced under Ni-stress, but with the application of CA, improvement was witnessed in their contents. The levels of malondialdehyde and hydrogen peroxide were enhanced with the increasing concentration of Ni, and after applying CA, they were reduced. The contents of antioxidants, i.e., catalase, peroxidase, superoxide dismutase, ascorbate peroxidase, dehydroascorbate reductase, and glutathione reductase, were increased at 50 ppm Ni concentration and decreased at higher concentrations of Ni. The application of CA significantly improved antioxidants at all concentrations of Ni. T